Risky Debt-Maturity Choice under Information Asymmetry - WU, Chunchi (Institutional Knowledge at Singapore Management University, 2007)
The traditional equilibrium models of signaling with debt-maturity require transaction costs by firms when raising new capital. In this paper, we propose a new model that has no such requirement. We demonstrate that a separating equilibrium of debt-maturity choice exists under a much more general condition, once accounting for the interactions between borrowers and lenders. The model is able to explain the observed complex financial structure. It is found that callable debt functions much like short-term debt, and serial debt similar to long-term debt. In equilibrium, high-quality firms issue short-term debt, and low-quality firms issue long-term debt.